2015
DOI: 10.1007/s11064-014-1486-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Recovery of the Injured Spinal Cord in Rats Treated with Gonadotropin-Releasing Hormone

Abstract: Several studies have shown that gonadotropin-releasing hormone (GnRH) have extra-pituitary roles, including neurotrophic effects. This study was to evaluate the effects of GnRH treatment on the spinal cord injury (SCI) of rats. Ovariectomized rats were divided into: sham SCI surgery (Sham), SCI treated with saline solution (SCI + SS), and SCI treated with GnRH (SCI + GnRH). The SCI was induced by compression. One day after the lesion, SCI + GnRH group was injected with GnRH (60 µg/kg/twice/day; i.m.) for 15 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…These data suggest possible roles of GnRH3 systems on locomotion or movement. Interestingly, studies on spinal cord injury also support locomotor effects of GnRH systems, showing that GnRH treatment to rats with experimentally induced spinal cord injury improves recovery, increases locomotor activity, and decreases histopathological damage in the injured spinal cord of rats (Calderon-Vallejo et al, 2015;Calderon-Vallejo and Quintanar, 2012).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These data suggest possible roles of GnRH3 systems on locomotion or movement. Interestingly, studies on spinal cord injury also support locomotor effects of GnRH systems, showing that GnRH treatment to rats with experimentally induced spinal cord injury improves recovery, increases locomotor activity, and decreases histopathological damage in the injured spinal cord of rats (Calderon-Vallejo et al, 2015;Calderon-Vallejo and Quintanar, 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies of spinal cord injury in rat models have used GnRH as a treatment for locomotion recovery (Calderon-Vallejo et al, 2015;Calderon-Vallejo and Quintanar, 2012). We tested the effects of a GnRH inhibitor (RFRP3) on locomotor behavior to examine if impacting the GnRH system would affect locomotion of 20 dpf larvae.…”
Section: Bpa Effects On Locomotor Behavior In 20 Dpf Larvaementioning
confidence: 99%
“…In relation to the functional effects of GnRH and LA, locomotion activity was evaluated in rats with SCI. The results showed a partial but significantly improvement in locomotor activity and gait related to stride length and stride speed (Calderón-Vallejo et al 2015, Calderón-Vallejo and Quintanar 2012, Díaz-Galindo et al 2015. Quintanar et al (2016b) reported a case of a male patient with chronic incomplete spinal cord injury (ASIA C) at level T-9 treated with LA during 12 months.…”
Section: Discussionmentioning
confidence: 95%
“…In the morphological study of spinal cord, both GnRH and LA treatment increased the number and caliber of nerve axons, and the white matter was well preserved in SCI rats (Calderón-Vallejo et al 2015, Díaz-Galindo et al 2015. In SCI, the plasticity of axons can be gained through processes of regeneration, where new axonal growth arises at the injury site from the cut end of an axon.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation